Demonstration of Equivalence of Generic Glatiramer Acetate and Copaxone® - Lipsky, Peter; Vallano, Patrick T.; Smith, Jeffrey; Owens, Walter; Snider, Daniel; Bandaru, Viswanath; Sun, Yunfu; Wallingford, Ross; Duncan, Joseph; Lewis, Joshua; Southall, Jason; Ansari, Azeem; et al. (Frontiers in Pharmacology, 2021)
The objective of the current work was to demonstrate the equivalence of Mylan’s glatiramer acetate (GA) to that of the reference product Copaxone® (COP) using the four criteria for active pharmaceutical ingredient sameness as established by the US Food and Drug Administration (FDA). The reaction scheme used to produce Mylan’s glatiramer acetate (MGA) was compared with that of COP, determined from publicly available literature. Comparative analyses of MGA and COP were performed for physicochemical properties such as amino acid composition and molecular weight distributions. Spectroscopic fingerprints were obtained using circular dichroism spectroscopy. Structural signatures for polymerization and depolymerization including total diethylamine (DEA) content, relative proportions of DEA-adducted amino acids, and N-and C-terminal amino acid sequences were probed with an array of highly sensitive analytical methods. Biological activity of the products was assessed using validated murine experimental allergic encephalomyelitis (EAE) models of multiple sclerosis. MGA is produced using the same fundamental reaction scheme as COP and was shown to have equivalent physicochemical properties and composition. Analyses of multiple structural signatures demonstrated equivalence of MGA and COP with regard to polymerization, depolymerization, and propagational shift. Examination of the impact on prevention and treatment of EAE demonstrated equivalence of MGA and COP with respect to both activity and toxicity, and thereby provided confirmatory evidence of sameness. A rigorous, multi-pronged comparison of MGA and COP produced using an equivalent fundamental reaction scheme demonstrated equivalent physicochemical properties, structural signatures for polymerization and depolymerization, and biological activity as evidenced by comparable effects in EAE. These studies demonstrate the equivalence of MGA and COP, establishing active ingredient sameness by the US Food and Drug Administration (FDA) criteria for GA, and provide compelling evidence that the FDA-approved generic MGA can be substituted for COP for the treatment of patients with relapsing-remitting MS.